Factorial analysis on bacillus Sp. removal using garlic solution - Siti Rahmah, Rahim (2016)
Biofilm is a complex structure adhering to surfaces that are regularly in contact with water, consisting of colonies of bacteria and other microorganisms. Many different microbes can be found in biofilm such as Bacillus sp., Listeria monocytogenes, Staphylococcus sp., Escherichia coli and many more. Bacillus sp. was used as biofilm model in this study. Garlic solution was used to remove Bacillus sp. In this study, garlic solution was prepared by crushing the garlic and mixed it with water. The selected factors were ratio of water to garlic (W/G) (1:1 and 1:5), ratio of garlic solution to Bacillus sp. (GS/B) (1:1 and 1:3), agitation speed (50-100 rpm) and reaction time between Bacillus sp. and garlic (12-24 hours). Design Expert software (Version 7) was used to construct experimental table where all the factors was randomized. The most contributing factor and interaction between the factors was analysed via two level factorial analysis by using the same software. The significant of this study is to find out which factors affect the most on Bacillus removal. From this study, the results showed that the most significance factors were GS/B and agitation speed, while for the interaction effect was between W/G and GS/B. As a conclusion, the Bacillus sp. removal best condition was determined at W/G at 1:1, GS/B at 1:3, agitation speed at 50 rpm and reaction time at 12 hours. The result of the best condition was 88.46% of Bacillus sp. removal. In a nutshell, the results did show the potential application of garlic solution on Bacillus sp. removal. Garlic solution can replace other commercial natural biocides especially in food industry.